Karyotype depends on sperm head morphology in some amniote groups - Kramer, Eric M.; Enelamah, Joshua; Fang, Hao; Tayjasanant, P. A. (Frontiers in Genetics, 2024)
The karyotype of an organism is the set of gross features that characterize the way the genome is packaged into separate chromosomes. It has been known for decades that different taxonomic groups often have distinct karyotypic features, but whether selective forces act to maintain these differences over evolutionary timescales is an open question. In this paper we analyze a database of karyotype features and sperm head morphology in 103 mammal species with spatulate sperm heads and 90 sauropsid species (birds and non-avian reptiles) with vermiform heads. We find that mammal species with a larger head area have more chromosomes, while sauropsid species with longer heads have a wider range of chromosome lengths. These results remain significant after controlling for genome size, so sperm head morphology is the relevant variable. This suggest that post-copulatory sexual selection, by acting on sperm head shape, can influence genome architecture.